Rwanda : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) Requests for Waivers of Nonobservance of Performance Criteria and Request for a New Three-Year Arrangement Under the PRGF Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report ;, 2006)
Policy implementation has improved since the completion point. Recent economic performance has been encouraging, but sustaining it will require an acceleration of reforms by the government. Rwanda's medium-term program aligned with the Poverty Reduction Strategy Program priorities provides an appropriate framework, but further refinements are needed. The main macroeconomic challenge is managing the domestic demand impact of fiscal policies. Executive Directors welcome the scope of structural reforms aimed at private sector development, improving public service delivery, and productivity-enhancing strategies in key sectors.